2017
DOI: 10.1002/adma.201702714
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Silver Nanoparticles for Seeded Lithium Deposition toward Stable Lithium Metal Anode

Abstract: To exploit the high energy density of the lithium (Li) metal battery, it is imperative to address the dendrite growth and interface instability of the anode. 3D hosts for Li metal are expected to suppress the growth of Li dendrites. Heterogeneous seeds are effective in guiding Li deposition and realizing spatial control over Li nucleation. Herein, this study shows that ultrafine silver (Ag) nanoparticles, which are synthesized via a novel rapid Joule heating method, can serve as nanoseeds to direct the deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
386
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(391 citation statements)
references
References 44 publications
5
386
0
Order By: Relevance
“…[144][145][146][147] However, this strategy loses 90% of the capacity contributing from Li metal anode and now cannot satisfy the urgent demand of high energy density devices. Exploring an efficient host for Li metal anode is quite crucial for a practical Li−S battery.…”
Section: Metal Protection In Li−s Batteriesmentioning
confidence: 99%
“…[144][145][146][147] However, this strategy loses 90% of the capacity contributing from Li metal anode and now cannot satisfy the urgent demand of high energy density devices. Exploring an efficient host for Li metal anode is quite crucial for a practical Li−S battery.…”
Section: Metal Protection In Li−s Batteriesmentioning
confidence: 99%
“…Reprinted with permission from Ref. [335], copyright 2017, Wiley-VCH. g Schematic of Li deposition and stripping processes with Cs + additive.…”
Section: Solvent-in-saltmentioning
confidence: 99%
“…In Hu's study, as shown in Fig. 15f, they modified the commercial carbon nanofiber (CNF) with ultra-fine silver (Ag) nanoparticles on the surface via a rapid Joule heating method, which served as a selective substrate for Li deposition [335]. Coinciding well with Cui's results, there is no nucleation overpotential for Li deposition on the Ag/CNF substrate and Li prominently nucleates and grows on the Ag nanoseeds, resulting in a uniform Li film along the CNFs during Li platting.…”
Section: Selective Depositionmentioning
confidence: 99%
“…[2,[6][7][8][9][10][11] However, even with the aid of these interfacial layers, uniform deposition is difficult as it is dependent on a plethora of external factors including ion diffusion, screw dislocation of atoms, and the morphology of the electrode surface. [14][15][16][17][18][19][20][21][22][23][24][25] This specific technique offers several advantages: [26] 1) the porous structure reduces the local current density and ensures sufficient Li ion flux; 2) the porous 3D skeleton accommodates the volumetric change of the Li anode during the plating and stripping progress; 3) Li is deposited on the interior of the 3D matrices, but not directly on the surface of the electrode, thus prohibiting dendrite growth. [14][15][16][17][18][19][20][21][22][23][24][25] This specific technique offers several advantages: [26] 1) the porous structure reduces the local current density and ensures sufficient Li ion flux; 2) the porous 3D skeleton accommodates the volumetric change of the Li anode during the plating and stripping progress; 3) Li is deposited on the interior of the 3D matrices, but not directly on the surface of the electrode, thus prohibiting dendrite growth.…”
Section: Introductionmentioning
confidence: 99%